The Influence of Managerial Decision Making on the Effectiveness of Nursing Services - Rossa, M. Adila; Darmojo, Hardjito S; Fairuza, Filda (J I K O (Jurnal Ilmiah Keperawatan Orthopedi), 2019)
Managerial decision-making is a core competency in nursing management that plays a crucial role in determining the effectiveness of nursing services. Decisions made by nursing managers influence resource management, team coordination, quality of care, and patient safety. This study aims to explore in depth the influence of managerial decision-making on the effectiveness of nursing services in hospitals. This study used a qualitative approach with a phenomenological design. Participants consisted of nursing managers, ward heads, and senior nurses selected using purposive sampling based on their experience and involvement in the managerial decision-making process. Data were collected through in-depth interviews, participant observation, and managerial document review. Data were analyzed using thematic analysis to identify key patterns and themes emerging from participants' experiences. The results identified five main themes: decision-making as a determinant of the direction of nursing services, the influence of managerial competence and experience on decision quality, the importance of nurse participation in the decision-making process, the role of data-driven decisions in improving service quality and safety, and the direct impact of managerial decision-making on the effectiveness of nursing services. Appropriate, participatory, and evidence-based decisions have been shown to improve team coordination, the smoothness of nursing care, and overall service quality. This study concludes that strengthening managerial decision-making capacity is a key factor in increasing the effectiveness of nursing services and should be a focus in developing nursing management in hospitals.